PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS XI PADA MATERI SISTEM PEREDARAN DARAH MANUSIA MA PP. HASANATUL BAROKAH TAMBUSAI ROKAN HULU TAHUN PEMBELAJARAN 2014/2015 - -, Khairani; Lestari, Rena; Ade, Filza Yulina (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
The study to determine the effect of cooperative learning team assisted individualization (TAI) on learning outcomes biology class XI MA PP. Hasanatul barokah. This is a quasi- experimental study with a sample of students class XI A and XI B. the design study control group postest-only design. The result of the analysis of data obtained an average of 79,8 experimental class learning outcomes and grade control 78. Can thus be concluded that the implementation of cooperative learning team assisted individualization (TAI) provides a positive effect on learning outcomes biology class XI MA PP. Hasanatul Barokah.